An Analysis of a Medical Malpractice Case Caused by Ignoring the Obligation of Instruction during Surgery. (July 2014) - Wei, Liangyu; Sun, Pengcheng; Luan, Xiaolin; Li, Chao
Abstract The patients' right to informed consent has been paid more and more attention by a wide cross- section of society, which also means higher requirements for doctors in fulfilling the obligation of instructions. The experience of mediating medical malpractice prompts doctors to notice that fulfilling the obligation of instructions effectively should be a dynamic process that has always run through the medical act. It is especially easy to overlook and forget to inform the patient or family members about the intraoperative accident. By analyzing a relevant typical medical malpractice case, this paper discusses the issues related to fulfilling the doctors' obligation of instructions in surgery, and reflects on different infringements of patients' right to informed consent.